(untitled) (Malaysian Journal of Learning and Instruction, 2010)
Purpose – This study examined the effectiveness of peer tutoring in the teaching of Mathematics in a Malaysian government secondary school. This study also investigated the effects of peer tutoring on interest in learning mathematics, perceptions of instructional methods and mathematics self-efficacy, as well as gender differences for the various variables. Method – This study utilised the pretest-posttest with control group quasi-experimental research design. Two form four classes were randomly assigned to be taught using peer tutoring, and taught using lectures and exercises. The research instruments used in the study were a pretest, a posttest, and a questionnaire. Findings – Results showed that students who received peer tutoring had higher gain scores in the mathematics achievement tests compared to those receiving traditional instruction. In addition, female students performed better in the mathematics achievement tests. However, there was no interaction effect between gender and instructional methods used. Students in the peer tutoring groups showed higher interest in learning mathematics and mathematics self-efficacy. They also showed positive perceptions toward peer tutoring. In the peer tutoring group, female students showed higher interest in mathematics than male students. However, gender differences were not evident for mathematics self-efficacy and perceptions toward peer tutoring. Thus, it could be concluded that peer tutoring is a potentially effective instructional method that could be practised in secondary mathematics teaching and learning in Malaysian schools in tandem with other existing instructional methods. Value – Peer tutoring has not been widely studied in the context of the Malaysian classroom. This paper provides empirical findings supporting the effectiveness of peer tutoring as an instructional approach in enhancing students’ learning of mathematics irrespective of gender. In addition, peer tutoring can also augment students’ interest toward learning mathematics and their mathematics selfefficacy.